Климатические характеристики некоторых опасных явлений погоды на территории Пермского края (Географический вестник=Geographical bulletin, 2017)
Рассматриваются пространственные особенности различных статистических характеристик гроз, града, метелей и туманов на территории Пермского края. Приводятся данные о продолжительности явлений, их экстремальных особенностях. Прослеживаются временные изменения климатических характеристик явлений на протяжении 60 лет XX в.К л ю ч е в ы е с л о в а: метели; туманы; грозы; град; климатологическая обработка; циркуляционные условия; физико-географические условия; Уральские горы; Пермский край.THE CLIMATE CHARACTERISTICS OF SOME OF THE DANGEROUS NATURAL PHENOMENON WITHIN THE TERRITORY OF PERM REGION There are different spatial phenomenons of statistical characteristics (storms, hail, fogs and snowstorms) within the territory ofPermregion are being looked trough. There is data information regarding the phenomenon’s duration and its extreme characteristics is being brought in. Also, the time frame change of climate characteristics are being reviewed and constantly monitored for the past 60 years. Keywords: snowstorm, fog; storm; hail; climatic handling/processing; physic-geographical conditions; Ural mountains; Perm region.